Group counseling with behavioral contract technique: is it effective to reduce academic procrastination among junior high school students? - Alfiani Fernita Sari; Yulia Ayriza (Universitas Negeri Padang, 2022)
This study aims at knowing the effectiveness of group counseling with the behavioral contract technique to reduce academic procrastination among junior high school students. This study was a quasi-experimental design with a pretest-posttest nonequivalent control group in Ma'arif 9 Way Jepara Junior High School, East Lampung, Lampung Province. It involved 14 students who were determined through the purposive sampling technique. The data collection technique used an academic procrastination scale. The validity of the scale was assessed with content validity of expert judgment. The reliability test result of the academic procrastination scale with the Alpha Cronbach formula was 0.854. This study employed the non-parametric statistical data analysis techniques of the Wilcoxon and the Mann-Whitney test. The results showed that the group counseling with the behavioral contract technique was effective to reduce academic procrastination among the VIII grade students as evidenced with the value of Z = -3.134, p-value = 0.002 (p <0.05).